PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH PADA MATA PELAJARAN GEOGRAFI SISWA KELAS X IPS SMA NEGERI 2 KENDAL TAHUN PELAJARAN 2017/2018 - Amalia, Arifatun Rizka; Sriyanto, Sriyanto; Arifien, Moch (Edu Geography, 2020)
Learning is said to be successful if the learning objectives that formulated in the learning plan are successfullyachieved. The use of the right learning model makes it easier for students to understand the material.Geography learning using the Make a Match learning model allows students to learn with a pleasantatmosphere. The purpose of this study was to determine the effectiveness of using the Make a Match learningmodel on geography lesson viewed from student responses and student learning outcomes. The approach usedin this research is quantitative with the design of experimental research, which uses questions andquestionnaires as a data collection tool. The research population was X grade IPS students of SMA N 2Kendal with the students of class X IPS 1 and X IPS 2 as the sample. As a result, the experiment class thatreceived the Make a Match learning model got an average score of 83,47 while the control class got 81,38. Pembelajaran dikatakan berhasil apabila tujuan pembelajaran yang dirumuskan padarencana pembelajaran berhasil dicapai. Penggunaan model pembelajaran yang tepatmempermudah siswa dalam memahami materi. Pembelajaran geografi menggunakanmetode Make A Match memungkinkan siswa untuk belajar dengan suasana yangmenyenangkan. Tujuan dalam penelitian ini adalah untuk mengetahui efektifitaspenggunaan model pembelajaran Make A Match pada mata pelajaran geografi dilihatdari tanggapan siswa dan hasil belajar siswa. Pendekatan yang digunakan dalampenelitian ini adalah kuantitartif dengan desain penelitian eksperimen, yangmenggunakan soal dan angket sebagai alat pengumpul data. Populasi penelitian iniadalah siswa kelas X IPS SMA N 2 Kendal dengan sampel kelas X IPS 1 dan X IPS 2.Hasilnya eksperimen yang mendapatkan perlakuan metode Make a Match rata-rata hasilbelajarnya 83,47 dan kelas kontrol yang mendapat nilai rata-rata sebesar 81,38.